Etno-agronomi Pengelolaan Perkebunan Kopi di Sumberjaya Kabupaten Lampung Barat (Review) - EVIZAL, RUSDI (Agrotrop : Journal on Agriculture Science; Vol 3 No 2 (2013), 2015)
Ethno-agronomy of Coffee Plantation Management in Sumberjaya West LampungDistrict.Study of ethno-agronomy is important for policy making to support sustainable coffee plantationand ecological services in cathment area. This paper reviewed tradition across ethnic in Sumberjaya,West Lampung on coffee plantation management. It showed that the ethno-agronomy of coffee plantationsin Sumberjaya was a unique local wishdom. Coffee agronomic practices in Sumberjaya were evolutingand integrating with shifting cultivation system. Coffee treeswere rotated with vegetables crop or shrub.In Sumberjaya, land uses were dynamic between forests, coffee field, crop field, and shrubs. Pre-cropping and inter-cropping ofvegetables in coffee fieldwas source of income for farmers before coffeehad attainedphase of yielding. So far coffee plantations in Sumberjaya were managed by traditional andless intensive practices including by planting shade trees, timber and multi-purposes treespecies. Coffeeagroforestry was alocal wishdom that impotant for land conservation of the catchment area.
Keywords: agroforestry; coffee; ethno-agronomy; land use dynamic; shifting cultivation